Pelaksanaan Kepemimpinan Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Imam Bonjol Padang - Vivi Puspita Sari (Majalah Ilmiah UPI YPTK, 2019)
On the basis of preliminery field observatioan, the researcher noticed that the head of STISIPOL Imam Bonjol Padang was neither administrativel not academically capable to manage the institution. This condition may not continue should the STISIPOLwant to change institution to a better and modern academic human resource. The researce put its focus on how the head of STISIPOL behaved in the process of decision - making, one of the key aspect of management. The specific research question read follow, a). how the head of STISIPOL Imam Bonjol Padang behavedin decision making, b). what types of reactions of response were given by the academic and administrative staff toward leadership behaviour, c). what problems or handicaps were faced by the head of STISIPOL. This research was conducted by applying qualitative approach. In conclusion the research dare to say that it will be very hard to for STISIPOL Imam Bonjol Padang to change and improve unless the inner structure of personnel is revitalized including the change in the policy of academic staff recruitment.